The Relationship between Parenting Patterns and Learning Independence on Learning Outcomes of Elementary School Science Content - Puput Wijayanti; Desi Wulandari (Postgraduate, University of Mataram, 2024)
Problems in Grade IV of the Kartika Cluster State Elementary School, Blora Regency, show that science learning outcomes are still low. Based on interviews with teachers, it is hypothesized that factors that affect learning outcomes include Parenting and Learning Independence. The objectives of this study are: to examine the relationship between Learning Independence and science learning outcomes; to examine the relationship between Parenting Styles and science learning outcomes; to examine the relationship between Learning Independence and Parenting Patterns on students' science learning outcomes. This study uses a quantitative method with a type of correlation research. The results of the study showed: there was a positive and significant relationship between Parenting and Science learning outcomes with a contribution of 71.50%; there is a positive and significant relationship between Learning Independence and Science learning outcomes with a contribution of 70.80%; there was a positive and significant relationship between Parenting and Learning Independence together on students' science learning outcomes with a contribution of 73.10%. The conclusion in this study is that there is a positive and significant relationship between Parenting and Learning Independence on the learning outcomes of science students in Grade IV of the Kartika Cluster State Elementary School, Blora Regency. The suggestion in this study is that students are expected to be able to optimize the existing Learning Independence and Parental Parenting Patterns to improve learning outcomes.